Biosorption of Ni(II) Ions from Aqueous Solution Using Immobilised Cells of Bacillus cereus - Khairunnisa Khairunnisa; Ahmad Moh Nur; Dian Febrianti Pisceselia; Aulia Almag Fira; Putri Aldeani (International Journal of Engineering, Science and Information Technology, 2025)
In the present study, immobilised Bacillus cereus cells were used as a biosorbent for the removal of Ni2+ ions from aqueous solution. Bacillus cereus was immobilised with 3% sodium alginate and 2% CaCl2. The adsorption studies of bacteria were investigated in batch mode. Optimum biosorption conditions were determined as a function of pH, biosorbent dose, Ni2+ ion concentration, and contact time. The removal of Ni2+ ions increases with increased dose of biosorbent, while the adsorption capacity decreases with increasing dose of biosorbent. The equilibrium adsorption data were analysed using the Langmuir and the Freundlich isotherm models. The regression coefficient (R2) for the Langmuir isotherm was 0.9822 at a contact time of 60 minutes and pH 6. The maximum monolayer adsorption capacity (qe) of the biosorbent, as obtained from the Langmuir adsorption isotherm, was found to be 57.80 mg/g with the Langmuir adsorption constant ( 0,086 L/mg. RL values range from 0 to 1, as shown, supporting the previous observation that the Langmuir isotherm was favourable for Ni2+ ion adsorption. The adsorption kinetics were analysed using the pseudo-first-order and pseudo-second-order models. Kinetics of Adsorption followed pseudo-second order with a regression coefficient of pseudo-second order of  R2 0.98, the coefficient of rate constant for pseudo-second order () obtained 0.004 g/mg.min, pointing out that the adsorption mechanism is chemosorption or ion exchange. FTIR spectrum of biosorbent revealed the presence of OH, NH, C-H, C=O and COO-. SEM-EDX was used to analyse the surface morphology and texture of the biosorbent.